Understanding international students’ well-being in China: A mixed method analysis of health challenges and opportunities - Iqbal, Kashif (Journal of International Students, 2026)
This study investigates the challenges international students in China face in accessing healthcare services using a mixed-methods approach. Data from 384 students at Nanjing universities and 22 interviewees reveal that health-related difficulties are driven primarily by language barriers (89% agreement; M = 1.8, SD = 0.9) and financial constraints (73%; M = 1.9, SD = 0.8). Additionally, 56% of participants expressed dissatisfaction with the mandatory insurance system (p < 0.001), particularly regarding limited coverage for specialized care. Students also reported challenges in navigating traditional Chinese medical practices (M = 2.3/5), which further restricted healthcare utilization. While university medical facilities are generally viewed positively (78%), their effectiveness is constrained by inconsistent English proficiency among staff and limited mental health support. A significant proportion of students (70%; r = 0.62; p < 0.001) rely on peers for healthcare guidance, highlighting informal support networks. The findings underscore the need for expanded insurance coverage, improved multilingual and culturally competent services, and formalized peer support systems to promote equitable healthcare access for international students in China.